Brand image, price, and product quality On the purchasing decisions of swallow products PT. Garuda Mas Perkasa - Andre Marulitua Purba; Rahmat Alamsyah Harahap; Ghina Ambarwati; Lira Gohanna Thread Simbolon (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
The methods of collecting data with interviews, questionnaires, and documentation studies. The analysis method is multiple linear regression with classical assumption testing, namely normality, multicollinearity, and heteroscedasticity. The research population was 230 customers, the sample with simple random sampling was 146 respondents and 30 respondents were tested for validity and reliability. The method used is descriptive quantitative, the research nature is explanatory research. The conclusion of the effect of the brand image, price, and product quality simultaneously (Test F) has a positive effect on purchasing decisions of Fount 111.892 > F Fable 2.67 with a sig. of 0.000 < 0.05. Partially (test the brand image of t count 0.756 < table 1.655 and a sig. of 0.451 > 0.05, the price of count 3.561 > table 1.655 and a sig. of 0.001 < 0.05, the product quality of count 11.223 > table 1.655 and a sig. of 0.000 < 0.05. The results of the determination coefficient test of Adjusted R Square of 0.696, means that the brand image, price, and product quality affect purchasing decisions with a level of 69.6%, while the remaining 30.4% are ot